Anticoagulant Therapy in Initially Low‐Risk Patients With Nonvalvular Atrial Fibrillation Who Develop Risk Factors. Issue 16 (18th August 2020) - Choi, Sun Young; Kim, Moo Hyun; Lee, Kwang Min; Cho, Young‐Rak; Park, Jong Sung; Kim, Seong Woo; Kim, Jin Kyung; Chung, Matthew; Yun, Sung‐Cheol; Lip, Gregory Y. H.
Abstract : Background: The CHA2 DS2 ‐VASc score has been validated for stroke risk prediction in patients with atrial fibrillation (AF). Antithrombotic therapy is not recommended for low‐risk patients with AF (CHA2 DS2 ‐VASc 0 [male] or 1 [female]). We studied a cohort of initially low‐risk patients with AF in relation to their development of incident comorbidities and their treatment on oral anticoagulation therapy. Methods and Results: We assessed data from 14 441 low‐risk patients with AF (CHA2 DS2 ‐VASc score of 0 [male] or 1 [female]) using the Korean National Health Insurance Service database, in relation to their development of incident stroke risk factors and adverse outcomes. The clinical end point was the occurrence of ischemic stroke, major bleeding, all‐cause death, or the composite outcome (ischemic stroke + major bleeding + all‐cause death). In our cohort, 2615 (29.1%) male and 1650 (30.3%) female patients acquired at least 1 new stroke risk factor during a mean follow‐up of 2.0 years. Among the patients with an increasing CHA2 DS2 ‐VASc score ≥1, male and female patients treated with oral anticoagulants had a significantly lower risk of ischemic stroke (male: hazard ratio [HR], 0.62 [95% CI, 0.44–0.82; P =0.003]; female: HR, 0.65 [95% CI, 0.47–0.84; P =0.007]), all‐cause death (male: HR, 0.67 [95% CI, 0.49–0.88; P =0.009]; female: HR, 0.82 [95% CI, 0.63–1.02; P =0.185]), and composite outcomes (male: HR, 0.78 [95% CI, 0.61–0.95; P =0.042]; female: HR, 0.79 [95% CI, 0.62–0.96; P =0.045]) than patients not treated with oral anticoagulants. Conclusions: Approximately 30% of patients acquired ≥1 stroke risk factor over a 2‐year follow‐up period. Low‐risk patients with AF should be regularly reassessed to adequately identify those with incident stroke risk factors that would merit thromboprophylaxis for the prevention of stroke and the composite outcome.